Close-coupling approach to antiproton-impact ionisation of H2 with analytical spherical averaging - Abdurakhmanov, I.; Kadyrov, Alisher; Fursa, Dmitry; Bray, Igor (Institute of Physics Publishing, 2014)
Integrated cross section for single ionisation of molecular hydrogen by antiproton impact has been calculated in a wide range of impact energies from 1 keV up to 2 MeV using a close-coupling approach. For the first time all possible orientations of the molecular target have been accounted for using an ab initio analytical spherical averaging technique. Obtained results are in good agreement with experiment.